Globalisasi dan Dinamika Lokal: Kondisi Keamanan Insani Pedagang Lokal di Sekitar Hipermarket Giant di Kota Malang - Dian Mutmainah (Jurnal Transformasi Global, 2015)
Abstract This article is part of a research that applied human security as a concept in a local situation. The research investigated whether the presence of Giant hypermart as a representation of foreign actor affects the human security of local traders around it. It is an important question because global interaction has been reducing the capability of the state to provide security to its citizen. In this case, the presence of Giant at one urban area in Malang City has inevitably put local traders into global economic competition.The findings of the research demonstrate that the locals’ understanding is insufficient to build solidarity in order to create collective mechanism to survive the competition. One of the main reasons was because they merely saw the competition as a normal consequence of government policies. Indeed, it can be concluded that the guarantee of the fulfillment of locals’ human security also requires their understanding over their political rights to question government policies. Keywords: globalization, human security, economic security